A dinâmica fluvial quaternária e a configuração do modelado do relevo no contato entre a depressão do Rio Pomba e o Planalto de Campos das Vertentes - Zona da Mata de Minas Gerais - Leticia Augusta Faria de Oliveira (2012)
The study of superficial alluvial formations on the reconstitution of geomorphological events is an important tool in the comprehension of conditioning factors on the evolution of the draining system during the late Quaternary. The fluvial dynamics are very sensible to endogenous and exogenous alterations, and the fluvial sediments can keep records of the ongoing tectonic and climatic conditions in the sin and post depositional periods. The evolution of the drainage system is closely connected to the process of sculpture of the slopes and the comprehension about the space-temporary configurations of the drainage system supplies determinative information about the evolution of the relief. In Zona da Mata region, Minas Gerais state, the upper Pomba River basin (tributary on the left bank in the low course of Paraíba do Sul River) presents divergences regarding the morphology of the slopes in areas of similar lithology, and free of a recognized structural control. The configuration of the reliefs regional modeling suggests a decisive role of fluvial processes on the genesis of two distinct morphological compartments: the Pomba-Muriaé Rivers Scaled Depression and the Campos das Vertentes Plateau (PROJECT RADAMBRASIL, 1983). This dissertation evaluates the influence of the fluvial dynamics on the configuration of the depression in its contact with the plateau, as well as in its portion belonging to the aforementioned basin. Through the survey, characterization, interpretation and dating of actual and past fluvial sediments in the main water courses which drain both morphological compartments, it was possible to discuss the anthropic, structural, tectonic and climatic influences on the fluvial dynamics, as well as its influence on the modeling of the relief in the study area. Regionally, the fluvial geomorphology is set by the occurrence of three groups of abandoned fluvial levels: i) levels about 25 meters above the present river, identified only in the portions of the valleys near the Serra da Mantiqueira scarp; ii) levels between 15 and 20 meters above the river level, this height being increased towards the downstream. The occurrence of sediments on this level varies from valley to valley, although there is a regional standard of distribution; iii) thick terraces (on an average of 10 meters of thickness) that practically pass along the side of the whole fluvial flume and, in those terraces, the plains of anomalous amplitudes have been found nested or cut-in-bedrock, in several passages. The disposition and characterization of the fluvial levels indicate that their genesis was conditioned by differential Block Tectonic processes during the late Quaternary. The processes of river capture were common, through which rivers belonging to the Pomba River basin captured channels belonging to the Doce River basin. These processes would be responsible for the incorporation of areas of the plateau on Pomba River basin. The disposition of the flumes in rush stream obeys the structural or tectonic conditionality, and the recent incision of high courses suggests a continuity of the advancement of the depression on the plateau. The morphology of the floodplains occurs due to the combination of anthropic and tectonic factors, besides being influenced by the morphology on Pomba River basin. The dating of alluvial sediments through Optical Stimulated Luminescence (OSL) proved to be useful and adequate to date recent episodes of alluvial deposition (floodplains and terraces). Five among the six deposits of dated plain obtained between 1.500 (± 250) and 6.000 (± 750) years of age, being the plains of low courses older than those ones of high courses. At this period, the downcutting of the channel in the distance near the collection points it was null or inferior a meter. The age of 16.000 (± 1.500) years obtained for one of the deposits of the plain of the São Manuel River (plenty divergent, therefore, of those ones) may have been caused by the partial bleaching of the luminescence of quartz grains previously the deposition, resulting from the proximity between the local of the collection and the Serra da Mantiqueira scarp. For the dated terrace, it was obtained the age of 11.800 (± 1.000) years, during those years there was a downcutting of four meters of the water course. Characterizations of the study area, in which colluvial processes are frequent, can limit the temporary reach of this method, which could be efficient for dating more ancient episodes of fluvial deposition only in regions of steadier slopes.